A Longitudinal Study of Trajectories and Factors Influencing Patient-Reported Outcomes in Chronic Obstructive Pulmonary Disease - Cai M; Cui M; Nong Y; Qin J; Mo S (International Journal of COPD, 2022)
Mengqian Cai,1 Miaoling Cui,1 Ying Nong,2 Jinlian Qin,1 Sucai Mo1 1Department of Nursing, The First Hospital Affiliated of Guangxi Medical University, Nanning, People’s Republic of China; 2Respiratory Medicine, The First Hospital Affiliated of Guangxi Medical University, Nanning, People’s Republic of ChinaCorrespondence: Miaoling Cui, Tel +8613878134966, Email cuimiaoling@126.comPurpose: To explore the trajectory of patient-reported outcomes and the factors influencing them in patients with COPD.Patients and Methods: The study population, 236 patients with stable COPD who attended the outpatient clinic of the Department of Respiratory and Critical Care Medicine in a tertiary care hospital in Nanning City between October 2020 and November 2021, answered the modified patient-reported outcome scale for COPD (mCOPD-PRO). Patient-reported outcomes were investigated at the time of the patient’s outpatient visit (T1), 1 month after the visit (T2), 3 months after the visit (T3), and 6 months after the visit (T4). Latent class growth modeling was used to determine the number and shape of trajectories, and multinomial logistic regression analysis were used to explore influence factors of each class.Results: COPD patients’ reported outcome trajectories were classified into 3 categories: health low-level group (14.80%), health risk group (54.70%), and good health group (30.50%). Logistic regression analysis showed that gender, BMI, smoking history, number of comorbidities, whether it was their first visit, and lung function classification were influential factors in patients’ reported outcome trajectories (P< 0.05). Female, obese, had a history of smoking, number of comorbid diseases > 3, first diagnosis, and lung function class IV had a higher probability of entering the healthy low-level group.Conclusion: COPD patients have poor self-reported health levels during the first 6 months after the outpatient visit, and there is group heterogeneity in patient-reported outcome trajectories; medical staff should give patients specific nursing interventions based on their current development of COPD, self-reported changes, and other relevant influencing factors.Keywords: chronic obstructive pulmonary disease, patient-reported outcomes, trajectory, latent class growth model